2006
DOI: 10.1152/japplphysiol.01318.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser (Ga-Al-As 655 nm) on skeletal muscle fatigue induced by electrical stimulation in rats

Abstract: We investigated whether low-level laser therapy (LLLT) can reduce muscular fatigue during tetanic contractions in rats. Thirty-two male Wistar rats were divided into four groups receiving either one of three different LLLT doses (0.5, 1.0, and 2.5 J/cm2) or a no-treatment control group. Electrical stimulation was used to induce six tetanic muscle contractions in the tibial anterior muscle. Contractions were stopped when the muscle force fell to 50% of the initial value for each contraction (T50%). There was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
1
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 53 publications
(48 reference statements)
9
105
1
14
Order By: Relevance
“…Considerando os critérios de inclusão adotados, foram encontrados um total de 30 estudos nas bases de dados consultadas, dos quais quinze (50%) foram realizados em tendão 3,4,6,9,[22][23][24][31][32][33][34][35][36][37][38] , dez (33,33%) em musculos 12,14,[39][40][41][42][43][44][45] , e cinco (16,66%) em osso e/ou articulação 13,25,[46][47][48] Os resultados mais expressivos obtidos com a terapia foram: diminuição da resposta inflamatória mediante redução de células inflamatórias e modulação de mediadores da inflamação (36,66%), e o aumento da síntese de colágeno (13,33%). Alguns dos demais resultados (50,01%) mencionados foram: angiogênese; redução do estresse oxidativo, do colágeno e da fibrose; aumento do tecido de granulação, da remodelação e síntese óssea, assim como da expressão da proteína da diferenciação miogênica (MyoD) e do fator de crescimento endotelial vascular (VEGF).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Considerando os critérios de inclusão adotados, foram encontrados um total de 30 estudos nas bases de dados consultadas, dos quais quinze (50%) foram realizados em tendão 3,4,6,9,[22][23][24][31][32][33][34][35][36][37][38] , dez (33,33%) em musculos 12,14,[39][40][41][42][43][44][45] , e cinco (16,66%) em osso e/ou articulação 13,25,[46][47][48] Os resultados mais expressivos obtidos com a terapia foram: diminuição da resposta inflamatória mediante redução de células inflamatórias e modulação de mediadores da inflamação (36,66%), e o aumento da síntese de colágeno (13,33%). Alguns dos demais resultados (50,01%) mencionados foram: angiogênese; redução do estresse oxidativo, do colágeno e da fibrose; aumento do tecido de granulação, da remodelação e síntese óssea, assim como da expressão da proteína da diferenciação miogênica (MyoD) e do fator de crescimento endotelial vascular (VEGF).…”
Section: Resultsunclassified
“…Ainda com relação a enzimas, a redução da concentração sanguínea de CK observada em dois estudos adicionados a essa revisão sistemática foi adequada para uma melhor resposta na força muscular. Como a CK é marcadora muscular, sua diminuição indica redução da lesão tecidual 12 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…It stimulates the microcirculation, acts on tissue repair to reduce edema and pain (Mazzeto et al, 2007;Shinozaki et al, 2006). In addition, LLLT keeps the intensity of the force during muscle contraction and may delay its fatigue, and this may increase intracellular ATP levels sufficient to maintain muscle physical effort (Lopes-Martins et al, 2006). However, Gam et al (1993) have not shown efficiency of LLLT on musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%